Parenting teens with love and logic : preparing adolescents for responsible adulthood - Cline, Foster; Fay, Jim.; Cline, Foster (Colorado Springs, CO : c, 2006)
Explains how to parent teenagers not by punishing but by helping them understand real-world consequences for actions, focusing on preparing them for life on their own; provides practical guidance and sample conversations for specific situations.
Rev. ed. of: Parenting teens with love & logic. c1992.
Includes bibliographical references (p. 305-306) and index.
Keywords: Parent and teenager; Teenagers -- Family relationships; Adolescent psychology